Keck Planet Imager and Characterizer Emission Spectroscopy of WASP-33b - Luke Finnerty; Tobias Schofield; Ben Sappey; Jerry W. Xuan; Jean-Baptiste Ruffio; Jason J. Wang; Jacques-Robert Delorme; Geoffrey A. Blake; Cam Buzard; Michael P. Fitzgerald; Ashley Baker; Randall Bartos; et al. (The Astronomical Journal, 2023)
We present Keck Planet Imager and Characterizer (KPIC) high-resolution ( R ∼35,000) K -band thermal emission spectroscopy of the ultrahot Jupiter WASP-33b. The use of KPIC’s single-mode fibers greatly improves both blaze and line-spread stabilities relative to slit spectrographs, enhancing the cross-correlation detection strength. We retrieve the dayside emission spectrum with a nested-sampling pipeline, which fits for orbital parameters, the atmospheric pressure–temperature profile, and the molecular abundances. We strongly detect the thermally inverted dayside and measure mass-mixing ratios for CO ( ${logCO}_{MMR}=-{1.1}_{-0.6}^{+0.4}$ ), H _2 O ( ${logH}_{2}{{\rm{O}}}_{MMR}\,=-{4.1}_{-0.9}^{+0.7}$ ), and OH ( ${logOH}_{MMR}=-{2.1}_{-1.1}^{+0.5}$ ), suggesting near-complete dayside photodissociation of H _2 O. The retrieved abundances suggest a carbon- and possibly metal-enriched atmosphere, with a gas-phase C/O ratio of ${0.8}_{-0.2}^{+0.1}$ , consistent with the accretion of high-metallicity gas near the CO _2 snow line and post-disk migration or with accretion between the soot and H _2 O snow lines. We also find tentative evidence for ^12 CO/ ^13 CO ∼ 50, consistent with values expected in protoplanetary disks, as well as tentative evidence for a metal-enriched atmosphere (2–15 × solar). These observations demonstrate KPIC’s ability to characterize close-in planets and the utility of KPIC’s improved instrumental stability for cross-correlation techniques.